Effects of environmental heterogeneity on fish biodiversity and ecosystem functioning (BEF) relationships in the Yangtze River, China - Chang Xie; Jishun Ma; Hongwei Yao; Jun Wang; Qiong Zhou (Ecological Processes)
Abstract Background The relationships between biodiversity and ecosystem functioning (BEF) are of global concern due to unprecedented biodiversity loss. Although many controlled experiments advocate that biodiversity enhances ecosystem functioning, BEF relationships in natural ecosystems remain uncertain, especially in aquatic ecosystems. Specifically, how environmental heterogeneity shapes the effects of biodiversity on aquatic ecosystem functioning has been rarely researched. To address this issue, we explored the relationships among fish biodiversity, environmental factors, and ecosystem functioning (measured as productivity and decomposition) across different riverine zones (reference zone [RefZ], reservoir zone [RZ], and impacted zone [IZ]) along the Yangtze River mainstem (ca. 6300 km). Moreover, the relative importance of biodiversity and environmental factors to ecosystem functioning were evaluated. Results Our results indicated that diverse conditions along the riverine gradient drove spatial variability in fish biodiversity, with significantly lower functional diversity in RefZ. Moreover, divergent patterns of BEF relationships and underlying mechanisms were detected across different zones. Specifically, productivity and decomposition increased with functional richness (FRic) in RefZ and RZ, respectively, suggesting a complementarity effect that appeared critical for maintaining high ecosystem functioning. Conversely, in IZ, decomposition exhibited negative relationships with functional evenness (FEve) and divergence (FDiv), indicating dominance-driven selection effect underlying the BEF relationships. Contrary to our prediction, environmental factors explained more variation in ecosystem functioning than biodiversity across all zones. Despite the overall lower diversity, we found that biodiversity exhibited the greatest relative contribution to ecosystem functioning in the RefZ, highlighting its crucial role in sustaining ecosystem functioning in less-disturbed ecosystems. In addition, greater contributions of biotic factors to biodiversity and ecosystem functioning in RefZ was mainly attributed to the role of plankton communities in supporting aquatic consumers. Conclusions Our findings suggested that BEF relationships and their underlying mechanisms were context-dependent and varied across different riverine zones, emphasizing the necessity of zone-specific and perhaps even habitat-specific conservation strategies. Although environmental factors primarily regulated ecosystem functioning across all reaches, the relative contribution of biodiversity and biotic factors was more pronounced in less-disturbed zones. To enhance the ecosystem resilience against global change, we advocate the priority of heterogeneous habitat conservation in aquatic ecosystem management.